Multidrug-resistant Clostridium difficile ribotypes 078 and 014/5-FLI01 in piglets from Costa Rica. (February 2019) - Andino-Molina, Mauricio; Barquero-Calvo, Elías; Seyboldt, Christian; Schmoock, Gernot; Neubauer, Heinrich; Tzoc, Edgardo; Rodríguez, César; Quesada-Gómez, Carlos
Abstract: Though an overlap of Clostridium difficile PCR ribotypes (RT) in humans and animals has been noted -particularly in piglets-information regarding C. difficile isolates from swine is scarce in Latin America. A characterization of 10 C. difficile isolates obtained from this origin in Costa Rica revealed the presence of the RT078 (n = 4) and RT014/5-FLI01 (n = 6) ribotypes. Unlike two previous reports from the region, all isolates were multidrug resistant (MDR). According to a minimum spanning tree (MST) analysis, our RT078 isolates formed a clonal complex with some German RT078 isolates and the already noted overlap of RT078 strains in humans and animals. This unanticipated high level of genetic relatedness confirms the transcontinental spread and geographically unlimited clustering of RT078. Highlights: Multidrug-resistant C. difficile isolates were recovered in piglets from Costa Rica. The isolates belonged to RT078/NAP7 and RT014/5-FLI01 genotypes. Some RT078 isolates had MLVA profiles previously seen in human isolates. The results confirm the transcontinental dissemination of the RT078/NAP7 genotype.